PENERAPAN GREEN CHEMISTRY PADA PRAKTIKUM KIMIA PANGAN (MATERI ANALISIS PEMANIS BUATAN DALAM MINUMAN RINGAN) - A. Wijayanto A. Wijayanto (UIN Sunan Kalijaga Yogyakarta, 2018)
Green chemistry is the application of the principle of the removal and reduction of hazardous compounds in the design, manufacture and application of chemical products. Artificial sweeteners such as cyclamate has a sweetness and an economical price than natural sweeteners, that the use of it is great demand in various segments of society, including industry. The purpose of this study was to do the parameters of validation test of analytical method of cyclamate in soft drinks by High Performance Liquid Chromatography. Parameters of selectivity, precision, accuracy, limit of detection and limit of quantification will be reported to confirm this method deserves to be applied as a standard testing methods according to the rules of ISO/IEC 17025:2008. The results show the analysis of cyclamate in energy drinks can be determined using High Performance Liquid Chromatography UV detector as a standard method. Test method parameters obtained by the selectivity at a retention time of 5 minutes, the linearity of the calibration curve is shown with standard cyclamate at a concentration of 9.83 mg/L - 1016.44 mg/L with a correlation coefficient (R2) of 0.999, limit of detection of 28.24 mg/L and the limit of quantification of 176 m/L, precision of 1.023% and % of recovery as accuracy value of 95.27% - 102.76%.